Student’s Worksheet Practically by Using Discovery Learning Model to the Ability of Understanding Concept and Mathematics Problem Solving at Grade VII Grade of SMPN 38 Padang - Teni Suriani; Dewi Devita (Indonesian Operations Research Association (IORA), 2020)
The ability of understanding mathematical concept and problem-solving mathematics is one of aims of mathematic subject it is expected to develop in mathematics learning. Based on the observation that was doing by students of VII grade SMPN 38 Padang in 2019/2020 academic years, this research obtain that the students got difficulty in doing story problem that related in real life situation without illustration’s picture. It causes, mathematics learning still focused on text book and LKPD. LKPD that SMPN 38 Padang has still less variation and there is no step to find out and construct by their own learning concept. One of learning models that can be developed is discovery learning. Discovery learning is a learning model that can be informed by discovering process. The aims of this research are to obtain and develop LKPD by using discovery learning that is practicable. Thetype of the research use development research with formative evaluation type that according to Tesmer view. Practicality of LKPD is limited on field test step which giving practical questionnaire to students and teachers. The result of practicality of LKPD from teacher is 85% with very practical category and from the student is 85.30% with very practical category.